2020
DOI: 10.4317/jced.56145
|View full text |Cite
|
Sign up to set email alerts
|

Genioplasty with surgical guide using 3D-printing technology: A systematic review

Abstract: Background: The purpose of this systematic review is to evaluate the current state of the art of making genioplasties using 3D printing technology. Material and Methods: A multi-database single-reviewer systematic review identified sixteen papers that fulfilled the selection criteria. There were mainly case series and case reports available (Level IV of the Oxford Evidence-based medicine scale); only two prospective study (Level III) evaluated this subject. These articles are analyzed in details and summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Surgical accuracy can be significantly improved using CAD/CAM techniques [ 22 ]. Most authors agree that these new systems provide an excellent level of accuracy in OGS that is generally higher than that obtained using classic methods [ 8 , 10 , 22 , 23 , 24 ]. Nevertheless, the quality of the surgical results is still determined by the individual surgeon’s skill in executing the surgical plan.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Surgical accuracy can be significantly improved using CAD/CAM techniques [ 22 ]. Most authors agree that these new systems provide an excellent level of accuracy in OGS that is generally higher than that obtained using classic methods [ 8 , 10 , 22 , 23 , 24 ]. Nevertheless, the quality of the surgical results is still determined by the individual surgeon’s skill in executing the surgical plan.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, the quality of the surgical results is still determined by the individual surgeon’s skill in executing the surgical plan. However, many studies have shown that clinicians can increase surgical safety, shorten the operative duration, and improve the predictability of the surgical results using patient-specific systems based on 3D technology [ 22 , 23 , 24 ]. Recently, 3D color mapping has enabled 3D visualization of the skeletal changes to the condyle after surgical manipulation of the jaw bones, and this technique can be applied to monitor positional changes of the condyle.…”
Section: Discussionmentioning
confidence: 99%
“…The next stage of development and search for new applications for additive manufacturing technologies are 3D models used as surgical templates or guides (13)(14)(15). They are made based on computed tomography (CT) of a given patient, so they are patient-specific devices.…”
Section: Introductionmentioning
confidence: 99%